A novel formula for the quality factor calculation for the multiphase microwave dielectric ceramic mixtures. Issue 10 (August 2017) - Chen, Hetuo; Tang, Bin; Zhong, Chaowei; Yuan, Ying; Zhang, Shuren
Abstract: Microwave dielectric ceramics are pillar materials in the microwave applications, for example, resonators. However, because most ceramics possess non-zero temperature coefficients, two or more ceramics, with temperature coefficient of opposite signs, are always mixed as a multiple phase system to obtain a zero temperature coefficient ceramic. While the dielectric constant can be calculated by the Maxwell-Wagner based formula, the quality factor ( Q ) is usually hard to be precisely calculated by the conventional method. In this paper, basing on the classical dispersion theory, we derive a new formula for the Q calculation for the ceramic mixtures. The deviation between the calculated and reported Q, of several typical ceramic systems, is around ±5%, for the example of two phases ceramic mixtures.